2018
DOI: 10.1177/1556264618767780
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Parents’/Guardians’ Initial Comprehension and 1-Day Recall of Elements of Informed Consent Within a Mozambican Study of Pediatric Bacteremia

Abstract: Participants' understanding of key elements of a research protocol is essential to their ethical enrollment in the study. Ongoing participation should be based on continued comprehension and consent, which presumes a high degree of recall. Many obstacles can prevent full understanding of information about the research protocol. This study's aim was to evaluate the comprehension and 1-day recall of the elements of informed consent by the parents/guardians of children enrolled in a clinical study in Mozambique. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…A study carried out in India (19) , which aimed to assess the quality of informed consent among participants in cancer clinical trials, showed that the mean of correct responses was 60.46%. This result is similar to that found in a systematic review, which identified that the proportion of participants in clinical trials who understood different components of informed consent ranged from 52.1% to 75.8% (10). These findings indicate that, despite advances in the area, the problem of misunderstanding remains constant in different scenarios (4,14) .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A study carried out in India (19) , which aimed to assess the quality of informed consent among participants in cancer clinical trials, showed that the mean of correct responses was 60.46%. This result is similar to that found in a systematic review, which identified that the proportion of participants in clinical trials who understood different components of informed consent ranged from 52.1% to 75.8% (10). These findings indicate that, despite advances in the area, the problem of misunderstanding remains constant in different scenarios (4,14) .…”
Section: Discussionsupporting
confidence: 85%
“…The quality of the informed consent process in vaccine clinical research can be determined by the participants' degree of understanding (9) . Adequate understanding requires the participant's ability to understand the action and nature of the study, the basic elements of a research protocol, among which are the possible risks and benefits, in addition to predicting its future consequences (10) . There are indications of gaps in terms of participants' understanding of information from clinical vaccine research (11)(12)(13)(14)(15) , attested both in developed and developing countries (16) .…”
Section: Introductionmentioning
confidence: 99%
“…Our study adds to the growing body of evidence related to the need for tailored informed consent processes in developing country contexts (Ossemane et al, 2018;Addissie et al, 2014). It must be noted that the contractual documentation of the informed consent process is probably insufficient for building trust and should be considered a minimum effort toward that end (Tomori, 2018).…”
Section: Informed Consent Concerns and Recommendationsmentioning
confidence: 89%
“…These include: the nature and scope of the research; the existing knowledge and attitude of the parents/guardians to research in general; the relationship between the parents, children and the researchers; and finally, the quality of communication between them. Full parental/guardian understanding of the core components of a proposed research project is essential for obtaining informed consent when enrolling children in such studies (Ossemane et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In Ghana, O [ 57 ] reported varied comprehension levels of disclosed information among participants and variability was also observed among younger and older participants. In Mozambique and South Africa, Ossemane et al [ 61 ] and Fischer et al [ 62 ], indicated that readability of IC was influenced by long sentences, the number of words containing three or more syllables of words per sentence resulting in poor comprehension. In South Africa the study by Fischer et al [ 62 ] showed that two-thirds of the ICFs analysed for readability did not meet recommendations by the national ethical guidelines stipulations, and that the IC documents were hard to read and exceeded the South African national functional literacy level of grade 7, equivalent to end of primary school level education.…”
Section: Methodsmentioning
confidence: 99%